Synthesis of (Zn/Co)‑based zeolite imidazole frameworks and their applications in visible light‑driven photocatalytic degradation of Congo red - Nguyen Thi Thanh Tu; Phung Chi Sy; Tran Thanh Minh; Huynh Thi Minh Thanh; Tran Vinh Thien; Hoang Thai Long; Dinh Quang Khieu (My University, 2019)
Synthesis of (Zn/Co)‑based zeolite imidazole frameworks and their applications in visible light‑driven photocatalytic degradation of Congo red
Keywords: Zn/Co-based ZIFs